Analisa Peralihan Deviasi Frekuensi Sistem Kendali Frekuensi Tenaga Listrik dengan Metoda Kendali Optimal - Heru Dibyo Laksono (Jurnal Rekayasa Elektrika, 2016)
This journal discusses about the analysis of frequency transition deviation of power frequency control system with Optimal control methods. The response of frequency transition deviation of power frequency control system is one of indicator in the performance of the power system during disturbances. These disturbances cause changes in the parameters value which result in power frequency control system will be disrupted and resulted system is not able to work normally after the disturbances. One of disturbance often occurs in power system is a sudden load changes. Sudden load changes cause of decreasing or increasing in the value of frequencies around the center of its operations. By using the optimal control method consists of Linear Quadratic Regulator (LQR) method and Linear Quadratic Regulator with weights function on the output (LQRy) are analyzed frequency transition deviation of power frequency control system type of Non-Reheat, Reheat and Hydraulic. The results obtained for the Linear Quadratic Regulator (LQR) method, the power frequency control system type of Non–Reheat has the smallest values of the transition parameter at the values of the transition parameter power frequency control system type of Reheat and Hydraulic. The values of the transition parameter power frequency control system type of Non-Reheat are 0.1266 seconds in time rise, 0.3451 seconds in settling time, 0.3451 seconds in peak time, 3.1972% in maximum overshoot and 0.0069 in peak value. For the Linear Quadratic Regulator method with weights function on the output (LQRy) power frequency control system type of Hydraulic has the smallest values of the transition parameter compared with the values of the transition parameter power frequency control system type of Non-Reheat and Reheat. The values of the transition parameter power frequency control system type of Hydraulic are 0.0451 seconds in time rise, 0.0731 seconds in settling time, 0.1300 seconds in peak time, 0.0531% in maximum overshoot and 0.0032 in peak value.